Lean-Driven Sustainable Engineering Enhanced by TRIZ: A Conceptual Approach to Waste Elimination in Manufacturing System Laboratory - Uly Amrina; Hendi Herlambang; Galang Persada Nurani Hakim; Irkham Syifaul Qulub; Lutfi Saputro (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Manufacturing system laboratories are essential in engineering education, however, existing laboratory-scale equipment often exhibits long cycle times, high energy consumption, poor ergonomics, and limited integration of sustainability principles. Prior studies generally address lean manufacturing, TRIZ-based innovation, or sustainable engineering separately, leaving a gap in a unified framework tailored for laboratory environments. This study aims to develop an integrated lean-driven sustainable engineering framework enhanced by TRIZ to systematically eliminate waste in a manufacturing system laboratory. A conceptual–experimental approach was adopted by combining lean waste analysis, TRIZ-based technical contradiction resolution, and sustainable engineering principles to redesign a modular Heating–Vacuum–Trimming (HVT) system. The proposed system was evaluated through prototyping and laboratory testing. The results demonstrate a reduction in process cycle time of up to 33% and a decrease in electrical energy consumption of approximately 16% compared to conventional equipment. From a practical perspective, the framework enables the development of modular, ergonomic, and energy-efficient laboratory tools that improve operational efficiency. From a theoretical perspective, this study extends the integrated application of lean manufacturing, TRIZ, and sustainable engineering into a cohesive framework suitable for laboratory-scale manufacturing systems. The proposed approach offers transferability.